Analysis of trochanteric fractures with a detached greater trochanter - Atsuo Furui; Nobuki Terada; Mitsuko Yamada; Shinichi Katou (Fujita Medical Journal, 2016)
Objectives: Trochanteric fractures with a detached greater trochanter are often encountered during routine medical examinations. We analyzed cases of stable reconstruction following surgery for these fractures. Methods: Forty-two patients who sustained a trochanteric fracture with a detached greater trochanter from 2015 to 2016 were clinically and radiographically reviewed. Fracture fixation was performed with 135° free-sliding plates. On postoperative day 14, the patients were classified into two groups based on their computed tomography findings: those in whom a lag screw could be inserted in the anterolateral part that continues to the diaphysis and those in whom the screw could not be inserted in this position. Outcome measures included the quality of reduction (postoperative neck–shaft angle on the lateral view, postoperative ratio of subtype A or subtype N according to Ikuta's classification), postoperative placement of the tip of the lag screw in the femoral head on the lateral view, and sliding distance of the lag screw on postoperative day 14. Results: The mean neck–shaft angle on the lateral view and the mean sliding distance of the lag screw were significantly shorter in the group in which the lag screw could be inserted in the anterolateral part that continues to the diaphysis. Conclusions: For trochanteric fractures with a detached greater trochanter, insertion of the lag screw in the anterolateral part that continues to the diaphysis is important and can achieve stable reconstruction. Moreover, caution should be employed with respect to the neck–shaft angle on the lateral view.